Retrobulbar and Tongue Base Pyogranulomatous Myositis Resulting in Strabismus in a Dog: Case Report - Sigmund, Alex B.; Hecht, Silke; Ward, Daniel A.; Hendrix, Diane V. H. (Frontiers in Veterinary Science, 2020)
A seven-year-old female spayed Australian Shepherd was presented for a three-day history of left eye ventromedial strabismus, episcleral injection, protrusion of the third eyelid, miosis, and enophthalmia. Magnetic Resonance Imaging (MRI) identified lesions in the left medial pterygoid muscle and left tongue base. Cytology and histopathology revealed pyogranulomatous inflammation with rod-shaped bacteria and pyogranulomatous myositis, respectively. One month of oral antibiotics resolved both lesions. Repeat MRI showed a mild decrease in size of the left medial pterygoid muscle consistent with fibrosis. Clinically, residual, positional ventral strabismus remained upon dorsal neck extension, but all other ophthalmic abnormalities resolved. To the authors’ knowledge, this is the first report of pyogranulomatous myositis causing this constellation of clinical signs and of repeat imaging depicting resolution of these lesions with therapy.